2000
DOI: 10.1074/jbc.m006325200
|View full text |Cite
|
Sign up to set email alerts
|

β2-Adrenergic Receptor-induced p38 MAPK Activation Is Mediated by Protein Kinase A Rather than by Gi or Gβγ in Adult Mouse Cardiomyocytes

Abstract: Increasing evidence shows that stimulation of ␤-adrenergic receptor (AR) activates mitogen-activated protein kinases (MAPKs), in addition to the classical G sadenylyl cyclase-cAMP-dependent protein kinase (PKA) signaling cascade. In the present study, we demonstrate a novel ␤ 2 -AR-mediated cross-talk between PKA and p38 MAPK in adult mouse cardiac myocytes expressing ␤ 2 -AR, with a null background of ␤ 1 ␤ 2 -AR double knockout. ␤ 2 -AR stimulation by isoproterenol increased p38 MAPK activity in a time-and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
88
2
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(93 citation statements)
references
References 32 publications
1
88
2
2
Order By: Relevance
“…We show that ␤ 2 -ARs stimulation induces a biphasic activation (early and delayed) of p38 MAPK, which is distinct from a previously described monophasic model in mast cells (1), fat cells, embryonic chick ventricular cells (4), and adult rat cardiac myocytes (8). Interestingly, early phase activation of p38 MAPK can be prevented by reducing the expression of ␤-arrestin-1 by siRNA and inhibiting NADPH oxidase activity.…”
contrasting
confidence: 54%
“…We show that ␤ 2 -ARs stimulation induces a biphasic activation (early and delayed) of p38 MAPK, which is distinct from a previously described monophasic model in mast cells (1), fat cells, embryonic chick ventricular cells (4), and adult rat cardiac myocytes (8). Interestingly, early phase activation of p38 MAPK can be prevented by reducing the expression of ␤-arrestin-1 by siRNA and inhibiting NADPH oxidase activity.…”
contrasting
confidence: 54%
“…Cytosols of HF stimulated with C1q display high levels of type I protein kinase A (PKA-I) (3). Given that in several systems p38 MAPK is a downstream target of the cAMP/PKA-I pathway, in cultures of HF, C1q-induced PKA-I activity may be a prerequisite for p38 signaling (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…neal injections of different doses of ISO (10,15,30, 50 mg/kg body weight) for 30 minutes, and heart tissues were rapidly harvested for analysis of MAPK signaling. We found that the phosphorylated levels of p38, SAPK/JNK, and ERK1/2 were significantly increased in both WT and Hsp20 TG hearts treated with various ISO doses; however, the degree of p38 and SAPK/JNK activation was significantly greater in WT hearts, whereas ERK was similarly activated in the 2 groups (Figure 4).…”
Section: Downregulation Of Iso-mediated Activation Of Stress Kinases mentioning
confidence: 99%